Propofol attenuates lung ischemia/reperfusion injury though the involvement of the MALAT1/microRNA-144/GSK3β axis - Jian-Ping Zhang; Wei-Jing Zhang; Miao Yang; Hua Fang (BMC, 2021)
Abstract Background Propofol, an intravenous anesthetic, was proven to protect against lung ischemia/reperfusion (I/R) injury. However, the detailed mechanism of Propofol in lung I/R injury is still elusive. This study was designed to explore the therapeutic effects of Propofol, both in vivo and in vitro, on lung I/R injury and the underlying mechanisms related to metastasis-associated lung adenocarcinoma transcript 1 (MALAT1)/microRNA-144 (miR-144)/glycogen synthase kinase-3β (GSK3β). Methods C57BL/6 mice were used to establish a lung I/R injury model while pulmonary microvascular endothelial cells (PMVECs) were constructed as hypoxia/reperfusion (H/R) cellular model, both of which were performed with Propofol treatment. Gain- or loss-of-function approaches were subsequently employed, followed by observation of cell apoptosis in lung tissues and evaluation of proliferative and apoptotic capabilities in H/R cells. Meanwhile, the inflammatory factors, autophagosomes, and autophagy-related proteins were measured. Results Our experimental data revealed that Propofol treatment could decrease the elevated expression of MALAT1 following I/R injury or H/R induction, indicating its protection against lung I/R injury. Additionally, overexpressing MALAT1 or GSK3β promoted the activation of autophagosomes, proinflammatory factor release, and cell apoptosis, suggesting that overexpressing MALAT1 or GSK3β may reverse the protective effects of Propofol against lung I/R injury. MALAT1 was identified to negatively regulate miR-144 to upregulate the GSK3β expression. Conclusion Overall, our study demonstrated that Propofol played a protective role in lung I/R injury by suppressing autophagy and decreasing release of inflammatory factors, with the possible involvement of the MALAT1/miR-144/GSK3β axis.